CONTACT WITH NATURE AS A PEDAGOGICAL RESOURCE IN EARLY CHILDHOOD EDUCATION (REMUNOM, 2025)
Contemporary childhood faces the challenge of excessive use of digital technologies and increasing detachment from the natural environment, which compromises children's holistic development. Screen mediation affects emotional bonds, autonomy, and sensory experiences, leading to what is known as the “nature deficit.” In response, several studies advocate for valuing contact with natural environments as a pedagogical axis in Early Childhood Education, promoting free play, identity formation, and environmental ethics. Given this context, the study aimed to demonstrate that contact with nature represented an essential pedagogical resource in Early Childhood Education, fostering children's integral development through sensory, emotional, and cognitive experiences. This qualitative study conducted a literature review on pedagogical practices that incorporate nature, highlighting their cognitive, emotional, and social benefits. School environments such as gardens, vegetable plots, and playgrounds were recognized as learning spaces that stimulate curiosity, responsibility, and connection with the environment. Outdoor activities supported neuropsychomotor development and skills such as empathy, imagination, and self-reflection. However, factors such as urban insecurity, overprotection, and lack of green areas limited children's access to nature, generating concerning impacts on health and quality of life. It was concluded that integrating nature into pedagogical practices is essential to forming healthier, more conscious individuals committed to sustainability.